Atención a la gestante con amenaza de parto prematuro y su Influencia en la prevención de complicaciones materno – Fetales. Hospital Minsa II– 2 Tarapoto. 2014 - Villarreal Flores, Lesly Janina (2015)
The present study: "attention to the pregnant woman with threat of preterm birth And its influence on the prevention of maternal complications - Fetales." Hospital MINSA II - 2 Tarapoto. 2014 ", study quantitative, not experimental, descriptive, Retrospective, cross-sectional, correlational design. Whose population was formed By 137 pregnant women. The results were, the incidence of preterm birth threat was 96 cases per 1000 Pregnant women treated in Hospital MINSA II-2 Tarapoto, population ranged from 20 to 39 years of age 78.8% (108), level of education secondary comprehensive 48.1% (65) and State civil partner 62.8% (86). In prevalence with 2 to 3 Pregnancies 51.8% (71), a history of infection tract urinary 48.2% (66). The 8.9% (12) studied with Placenta previa. The 94.7% (135) of pregnant women with APP, Did not have a timely diagnosis of prevention, since the diagnosis was after the 8 Week. Gestation, monitoring maternal fetal in 100%. 34.5% (51) culminated in Preterm birth. The 98.2% (135) of the pregnant women received drug treatment And drug not inappropriate. It is concluded that maternal complications of largest association in the study Population were: hemorrhage by uterine atony (p < 0,05) and perinatal Complication was: perinatal asphyxia and neonatal infection, neonatal death (p < 0,05), antenatal care significantly influence the prevention of perinatal maternal Complications.